2019
DOI: 10.1182/blood-2019-131336
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 and PKA/AMPK Axis Fuel Venetoclax Resistance in Lymphoid Cancers

Abstract: Venetoclax, the first approved BH3 mimetic targeting BCL2, demonstrates high response rate in chronic lymphocytic leukemia (CLL) but resistant cases are emerging. Aside from BCL2 mutations affecting venetoclax binding, multiple lines of mounting evidence suggest a role for non-mutational mechanisms underlying resistance to this drug. By applying both CRISPR-Cas9 knock-out and ORF overexpression screens in the lymphoma cell line OCI-Ly1, we previously reported the identification of MCL-1 overexpression and of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…While Liu et al. reported that the increase in MCL-1 expression is one important mechanisms for venetoclax resistance ( 35 ), others found that BCL-XL is a major regulator of this process in CLL ( 9 , 36 ). In line with our result, Haselager et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Liu et al. reported that the increase in MCL-1 expression is one important mechanisms for venetoclax resistance ( 35 ), others found that BCL-XL is a major regulator of this process in CLL ( 9 , 36 ). In line with our result, Haselager et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MCL-1 and BCL-XL in the resistance to venetoclax is still a matter of debate. While Liu et al reported that the increase in MCL-1 expression is one important mechanisms for venetoclax resistance (35), others found that BCL-XL is a major regulator of this process in CLL (9,36). In line with our result, Haselager et al demonstrated that there is a hierarchy of BCL-2 family members in CLL cells under the pressure of venetoclax, in which BCL-XL is dominant over MCL-1 in CLL venetoclax resistance when both are present (9,36).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests there is tremendous potential of venetoclax in treating hematologic tumors (54). The finding reported by R Guièze et al that venetoclax rapidly interferes with OXPHOS in sensitive CLL cells also further suggests that venetoclax effectively targets OXPHOS in lymphoid malignancies (24) to promote apoptosis in tumor cells (54). However, the resistance of venetoclax may be caused by the upregulation of OXPHOS.…”
Section: Increased Oxidative Phosphorylation Levelsmentioning
confidence: 93%
“…After venetoclax treatment, the changes in the relative expression of BCL-2, MCL-1, and BCL-XL, resulted in secondary drug resistance ( 22 , 23 ). Significantly elevated MCL-1 expression levels were observed in samples collected from patients who relapsed after venetoclax treatment, suggesting that it may be a mechanism to secondary drug resistance ( 24 ).…”
Section: Upregulation Of the Expression Of Non-bcl-2 Antiapoptotic Pr...mentioning
confidence: 99%
See 1 more Smart Citation